Os Efeitos De Sentido Do Termo Manifestação Nos Textos De Cartacapital E Folha De S. Paulo - Buzato, Anderson Da Silva [UNIFESP] (2018)
This Dissertation Aims To Investigate The Construction Of The Term Manifestação In Texts From Cartacapital (Also Cc) And Folha De S. Paulo (Fsp) In June 2013. In Addition, It Also Aims As For Specific Objectives To Elucidate, From The Discourse Use, The Generic Character Of The Claims In 2013, As Well As To Problematize The Way In Which The Genericity Of Things Corroborates To A Destabilization Of The Meaning Around The Lexeme Manifestação In Both The Newspaper And The Magazine. Starting From Events Occurred In Brazil In The Year 2013, The Lexeme Manifestação And Its Correlates, Atos, Protestos And Movimentos Present Effects Of Different Forms, In The Last Publications By Cartacapital And Folha De S. Paulo. While In Fsp We Observe The Meaning Effects Such As "Conflitos", "Baderna" And "Desordem". In Addition, The Lexemes, Subjects Of This Dissertation Are For Law Rights, Politic Acts, The Country Awakening From An Apathy Period With Rights Beeing Denied, The Achievements Of The Reduction Of The Transport Fare